1995
DOI: 10.1046/j.1471-4159.1995.64031379.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Treatment on Rate and Equilibrium Constants for [3H]Muscimol Binding to Rat Brain Membranes: Alteration of Two Affinity States of the GABAA Receptor

Abstract: Equilibrium binding curves were biphasic in control and ethanol‐treated rats. [3H]Muscimol binds to sites of high (KDA of ∼10 nM) and low (KDB of ∼0.3–0.4 µM) affinity. Chronic ethanol treatment produced a decrease in BmaxA value, and the hyperbolic binding profiles were progressively affected by the chronic and in vitro ethanol treatments, with most of this effect corresponding to the high‐affinity site. IC50 and Ki values were calculated for several competing ligands, using membranes from both control and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…4d). The binding affinities, number of [ 3 H]muscimol binding sites as well as binding kinetics are in the same range as found in the literature (Wang et al 1979;Agey and Dunn 1989;Maksay 1990;Negro et al 1995;Ebert et al 1999). However, because of the missing high-affinity d-receptors with slow kinetics, our association and dissociation rates in dKO fore/midbrain, dKO cerebellum, and recombinant a1b2c2 receptors are an exception as they were faster than all association rates in the former published studies.…”
Section: Dissociation Of [ 3 H]muscimol From Recombinant Gaba a R Subsupporting
confidence: 81%
See 1 more Smart Citation
“…4d). The binding affinities, number of [ 3 H]muscimol binding sites as well as binding kinetics are in the same range as found in the literature (Wang et al 1979;Agey and Dunn 1989;Maksay 1990;Negro et al 1995;Ebert et al 1999). However, because of the missing high-affinity d-receptors with slow kinetics, our association and dissociation rates in dKO fore/midbrain, dKO cerebellum, and recombinant a1b2c2 receptors are an exception as they were faster than all association rates in the former published studies.…”
Section: Dissociation Of [ 3 H]muscimol From Recombinant Gaba a R Subsupporting
confidence: 81%
“…In addition, chronic ethanol treatment leads to a substantial reduction in high‐affinity [ 3 H]muscimol‐binding sites (Negro et al . ), which meshes well with the notion that chronic alcohol leads to a reduction in δ‐GABA A R‐mediated tonic currents and δ‐subunit surface expression, a process that likely contributes to alcohol tolerance and the development of alcohol dependence (for review see Olsen and Liang ).…”
Section: Discussionsupporting
confidence: 71%
“…The decreased number of [ 3 H]muscimol binding sites in cerebral cortex observed after chronic ingestion in wild‐type mice is absent in knockout mice, suggesting that, as observed for NMDA receptors, the neuroadaptations of GABA A receptors following chronic ethanol are blunted in mice lacking CB1 receptors. A decreased number of high‐affinity sites for [ 3 H]muscimol has already been demonstrated in rat brain cortex after chronic ethanol treatment (Negro et al. 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Aim MUS is as highly selective GABA A R agonist (inhibition constant [K i ] = 2.7 nM; Negro et al 1995). We had previously shown that D 2 R-like imaging can be employed in order to estimate alterations of synaptic DA upon challenge with compounds such as methylphenidate and L-DOPA, which modify DA availability in the synaptic cleft (for review see Nikolaus et al 2011).…”
Section: Study 1: D 2/3 R Binding After Gaba a R Agonistic Treatmentmentioning
confidence: 99%